Effect of Lime Pretreatment on Microstructure of Cassava Stalk Fibers and Growth of Aspergillus niger - Dewi, Pramesti; Indrati, Retno; Millati, Ria; Sardjono, Sardjono (Biosaintifika: Journal of Biology & Biology Education, 2018)
Cassava stalk can be converted into sugar-based product by using microorganism. Unfortunately, lignin act as a barrier of optimal bioconversion. Cassava stalk needs pretreatment process for removing this barrier. The effect of lime pretreatment on microstructure of cassava stalk fibers and the growth of Aspergillus niger FNCC 6114 were observed in this research. The cassava stalks were reduced into 0.147- 0.297 mm size and pretreated with 1 % Ca(OH)2. Lime pretreated and unpretreated cassava stalk was used as solid medium for Aspegillus niger FNCC 6114. The effect of pretreatment method on fibers microstructure of cassava stalk was evaluated through SEM micrograph. The growth and metabolism activities of Aspergillus niger FNCC 6114 were monitored through SEM micrograph of media after fermentation. The other parameters examined were changes in glucosamine, reducing sugar levels, and sporesâ quantity. Lime pretreatment altered microstructure of cassava stalk fibers. However, cassava stalk without lime pretreatment gave better growth of Aspergillus niger FNCC 6144 based on metabolism activities parameters. Cassava stalks is suitable as media for Aspergillus niger FNCC 6144 through solid state fermentation. For better growth of Aspergillus niger FNCC 6144 fine-sized cassava stalk should not be lime pretreated. The results of this studyÂ  provideÂ  information about the pretreatment of cassava stems which was effective in supporting the growth of Aspergillus niger. Enhancements the utilization of cassava stems by using fungi, for example Aspergillus niger can overcome the accumulation of organic waste that can interfere with environmental sustainability.